Preservation of Clinically Relevant Accessory Renal Arteries in Infrarenal AAA Patients With Adequate Proximal Landing Zones Undergoing EVAR. (April 2016) - Abu Bakr, Nizar; Torsello, Giovanni; Pitoulias, Georgios A.; Stavroulakis, Konstantinos; Austermann, Martin; Donas, Konstantinos P.
Purpose: To report techniques to preserve the flow to relevant accessory renal arteries (ARA) in patients undergoing infrarenal endovascular aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA) with adequate landing zones.Methods: ARAs that originate inferior to the lowest ipsilateral main renal artery, supply one-third of the renal parenchyma, and having a diameter >4 mm have significant clinical importance. Between May 2012 and January 2015, among 389 high-risk patients with infrarenal AAAs who underwent standard EVAR, 9 (2.3%) patients each presented with a coexistent clinically relevant ARA. Their perfusion was secured by placing covered stents in the target ARA, parallel and outside of the main abdominal, as chimney grafts. Evaluation of acute and chronic renal decline was based on the consensus definition of RIFLE criteria (risk, injury, failure, loss, and end-stage) and chronic kidney disease (CKD) staging system, respectively.Results: The procedure was completed successfully in all cases. In the immediate postoperative period, no acute kidney injury was observed based on the RIFLE criteria. Eight of the 9 covered stents remained patent during a mean follow-up of 13.8±6.2 months. A single covered stent occlusion was observed 30 days postoperatively with infarction of the caudal pole of the kidney. This patient developed renal function impairment based on the CKD staging system 12 months after the initial procedure. For the remaining 8 patients, improvement of one CKD stage (n=1) or no change (n=7) in the CKD stage was observed.Conclusion: In AAA patients unfit for surgical revascularization, EVAR is associated with a significant decline in renal function. For this reason, preservation of relevant coexistent ARAs using the chimney technique should be considered as an option.